QRIS Adoption in West Java: Evidence from A Muslim-Majority Region - Maghfur, Abdullah; Indrawati (Journal of Islamic Economics and Business, 2026)
The unprecedented growth of digital payments has made the Quick Response Code Indonesian Standard (QRIS), introduced by Bank Indonesia, a crucial layer in Indonesia’s cashless infrastructure. As a Muslim-majority region with a high number of micro, small, and medium enterprises (MSMEs), West Java is an appropriate context for understanding the implementation of QRIS. This study synthesizes the existing literature on QRIS and digital payment adoption through a systematic review of UTAUT- and UTAUT2-based studies. The results demonstrate that performance expectancy, social influence, facilitating conditions, habit, and trust are most often identified as determinants of behavioral intention and usage behavior, while evidence on age and gender differences remains mixed. The review also reveals limited attention to sub-national and Muslim-majority regional contexts and conceptually integrates technology acceptance, trust–risk, and socio-religious perspectives to provide a more contextual understanding of QRIS adoption. These findings offer implications for future research and policy-making on regional digital payment ecosystems.